2005
DOI: 10.1590/s0034-89102005000300025
|View full text |Cite
|
Sign up to set email alerts
|

Métodos qualitativos e quantitativos na área da saúde: definições, diferenças e seus objetos de pesquisa

Abstract: The interest and accomplishments in qualitative research have been increasing in health. As a consequence, there is a greater demand for both institutional research programs and scientific journal publications. This article has the following purposes: (a) to present some definitions in qualitative methods used in Humanities and Health; (b) to compare them to the usual quantitative methods of health sciences; and, finally, (c) to illustrate the subject with the most important constructs in these methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
399

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(562 citation statements)
references
References 3 publications
(3 reference statements)
0
69
0
399
Order By: Relevance
“…From there, it was observed that the difference between the two approaches became increasingly large, with a predominance of qualitative methods from the 90's (5) . In the context of qualitative methodology applied to health, it is not sought to study the phenomenon itself, but to understand the individual or collective significance to people's lives (14) .…”
Section: Resultsmentioning
confidence: 99%
“…From there, it was observed that the difference between the two approaches became increasingly large, with a predominance of qualitative methods from the 90's (5) . In the context of qualitative methodology applied to health, it is not sought to study the phenomenon itself, but to understand the individual or collective significance to people's lives (14) .…”
Section: Resultsmentioning
confidence: 99%
“…Pode e deve ser utilizada como importante instrumento de apoio na promoção da saúde, aproveitando o espaço criado pelo PAE para analisar e discutir esses fatores e refletir sobre eles (Costa, Ribeiro e Ribeiro, 2001). Ao analisar, entre docentes, métodos qualitativos e quantitativos na área da Saúde, Turato (2005) confirma que o nutricionista é visto como educador em todas as áreas de atuação. Para os docentes, tal significado é compartilhado, podendo ser chamado de significado coletivo.…”
Section: Dos Achados E Suas Lições: A(o) Nutricionista Da Alimentaçãounclassified
“…Neste sentido, de acordo com Turato 13 , os métodos qualitativos apontam para um interesse do pesquisador em buscar o "significado das coisas, porque este tem um papel organizador nos seres humanos" (p. 510). O desenho de projeto pauta-se em recursos em aberto e flexíveis, procedimentos ajustáveis, com poucos sujeitos que representem as características de certa subpopulação.…”
Section: Métodounclassified
“…O desenho de projeto pauta-se em recursos em aberto e flexíveis, procedimentos ajustáveis, com poucos sujeitos que representem as características de certa subpopulação. 13 Quanto à pesquisa qualitativa em psicoterapia e psicanálise, Zaslavsky 14 defende que "a psicoterapia e a psicanálise (aqui incluída como uma psicoterapia) devem achar e/ou definir sua própria metodologia de pesquisa, e não tentar simplesmente adaptarse a métodos extraídos de outras ciências" (p. 238). Além disso, Calil e Arruda 15 argumentam que o estudo de um caso único ou de um pequeno número de casos clínicos é justificável, pois ao melhor especificar "as qualidades inerentes ao fenômeno humano, ganha também em amplitude utilizando-se não de esquemas rígidos de medição, mas da criticidade e da originalidade" (p. 198).…”
Section: Métodounclassified
See 1 more Smart Citation